2009
DOI: 10.1590/s0100-84042009000400021
|View full text |Cite
|
Sign up to set email alerts
|

Origin of successive cambia on stem in three species of Menispermaceae

Abstract: -(Origin of successive cambia on stem in three species of Menispermaceae). The lianas observed in this study, Abuta convexa (Vell.) Diels, Abuta imene (Mart.) Eichler, and Chondrodendron platiphyllum (A. St.-Hil.) Miers, all have successive cambia in their stems. The terminology applied to stem histology in species with successive cambia is as diverse as the interpretations of the origins of this cambial variant. Therefore, this study specifi cally investigates the origin of successive cambia through a develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…As for origin, they are always formed externally to the original vascular cylinder. The most common origin is from parenchyma of the outermost portion of the vascular cylinders, which in roots is unanimously recognized as the pericycle, while in stems it is recognized either as the pericycle or sometimes the cortex by those authors who do not believe in its presence there (Eames & McDaniels, , Tamaio et al, ; Terrazas et al, , Cunha Neto et al ). However, successive cambia can also derive from phloem parenchyma cells of the nonconducting secondary phloem, as shown in some Leguminosae (Nair & Mohan‐Ram, ; Dias‐Leme, ) or cortical cells beyond the limits of the vascular cylinder (Rajput et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As for origin, they are always formed externally to the original vascular cylinder. The most common origin is from parenchyma of the outermost portion of the vascular cylinders, which in roots is unanimously recognized as the pericycle, while in stems it is recognized either as the pericycle or sometimes the cortex by those authors who do not believe in its presence there (Eames & McDaniels, , Tamaio et al, ; Terrazas et al, , Cunha Neto et al ). However, successive cambia can also derive from phloem parenchyma cells of the nonconducting secondary phloem, as shown in some Leguminosae (Nair & Mohan‐Ram, ; Dias‐Leme, ) or cortical cells beyond the limits of the vascular cylinder (Rajput et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In these three species, approximately 8 -9 collateral vascular bundles (cvb) were present, and each collateral vascular bundle developed 1 -3 split strips (Figure 1(f); Figure 2(a) and Figure 2(b); arrows). A mature stem of Ungulipetalum filipendulum (Menispermaceae) was identified based on parenchyma proliferation [23]. The trait of 1 -3 split strips is related to the proliferation of non-lignified parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…MENEZES et al (2005) introduced a new interpretive proposal for the primary thickening meristem, describing the PTM as the pericycle in a meristematic phase, together with the endodermis and its derivatives. On the other hand TAMAIO et al (2009) concluded that meristematic conjunctive tissue of the Menispermaceae and the PTM are the same structure with different names.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is not only controversy about terminology, but also about the origin(s) of the successive cambia and their cambial derivatives as well as about the underlying growth patterns. Different ontogenetic interpretations have led to the distinct terminology (STE- VENSON & POPHAM 1973;MIKESELL & POPHAM 1976;MIKESELL 1973MIKESELL , 1979YARROW & PO-PHAM 1981;CARLQUIST 1988CARLQUIST , 2004CARLQUIST , 2007bRAJPUT et al 2009a;TAMAIO et al 2009).…”
Section: Introductionmentioning
confidence: 99%